Study of Lactic Acid Thermal Behavior Using Thermoanalytical Techniques - Andrea Komesu; Patricia Fazzio Martins Martinez; Betânia Hoss Lunelli; Johnatt Oliveira; Maria Regina Wolf Maciel; Rubens Maciel Filho (Journal of Chemistry)
Actually, there is a growing interest in the biotechnological production of lactic acid by fermentation aiming to substitute fossil fuel routes. The development of an efficient method for its separation and purification from fermentation broth is very important to assure the economic viability of production. Due to its high reactivity and tendency to decompose at high temperatures, the study of lactic acid thermal behavior is essential for its separation processes and potential application. In the present study, differential scanning calorimetry (DSC) analyses showed endothermic peaks related to the process of evaporation. Data of thermogravimetry (TG/DTG) were correlated to Arrhenius and Kissinger equations to provide the evaporation kinetic parameters and used to determine the vaporization enthalpy. Activation energies were 51.08 and 48.37 kJ·mol−1 and frequency values were 859.97 and 968.81 s−1 obtained by Arrhenius and Kissinger equations, respectively. Thermogravimetry, coupled with mass spectroscopy (TG-MS), provided useful information about decomposition products when lactic acid was heated at 573 K for approximately 30 min.